The Effectiveness of International Trade Conflict Resolution Law Through the World Trade Organization - Hutajulu, Marihot Janpieter; Nauli Hutajulu, Esther Priyanka (Indonesian Journal Publisher, 2025)
International trade is growing rapidly, as evidenced by the involvement of all countries in international trade. International trade involves various countries with different legal and judicial systems, such as civil law and common law. These differences often pose challenges in the drafting and implementation of international trade contracts. To address this, efforts to unify and harmonize laws have emerged through international institutions such as the United Nations Commission on International Trade Law (UNCITRAL). On the other hand, the resolution of international trade disputes has also become a major concern, particularly through the Dispute Settlement Body (DSB) mechanism within the World Trade Organization (WTO). This article aims to analyze how differences in legal systems affect international trade, the legal harmonization efforts undertaken, and the effectiveness of the WTO (World Trade Organization) dispute resolution mechanism in addressing conflicts between countries. The research findings indicate that the laws governing the resolution of international trade conflicts through the WTO remain quite effective in their implementation.